The epidemiology of cross country skiing injuries. Issue 15 (10th November 2011) - Howes, J; Droog, S J; Evans, J; Wood, I M; Wood, A M
Abstract : There is little literature about the epidemiology of injuries sustained while conducting cross country skiing due to the disparate nature of these athletes. The Royal Marines regularly deploys to Norway to conduct cross country ski-training and cold weather warfare training which presents a unique opportunity to analyse injuries sustained while conducting this sport. A total of 1200 personnel deployed to Norway in 2010 over a 14 week period. Patients who sustained injuries who were unable to continue training were returned to the UK. All data on personnel returned to the UK due to injury or illness was prospectively collected and basic epidemiology recorded. 53 patients (incidence 44/1000 personnel) were returned to the UK 20/53 (38%) of all cases were musculoskeletal injuries (incidence 17/1000 personnel). 15/20 musculoskeletal injuries were sustained while conducting cross country ski training (incidence 13/1000). Injuries sustained while skiing: 5/15 sustained anterior shoulders dislocation, 5/15 Grade 1–3 MCL/LCL tears, 2/15 sustained ACJ injuries, 1/15 crush fracture T11/T12, 1/15 tibial plateau fracture and 1/15 significant ankle sprain. The most common injury regardless of cause was anterior shoulder dislocation 6/20 (incidence 5/1000). Our results suggest that cross country ski training has a high injury rate requiring evacuation back to the UK. In our study group the high injury rate is possibly due to the rapid transition from non-skier to skiing with a bergen and weapon. Doctors covering Royal Marine training should have appropriate sports and exercise medical training, and rehabilitation units supporting the Royal Marines should expect sudden increases in referrals when large-scale cross country ski training is being conducted.